Anticancer efficacies of persicogenin and homoeriodictyol isolated from Rhus retinorrhoea. (August 2020) - Saquib, Quaiser; Ahmed, Sarfaraz; Ahmad, Mohammad S.; Al-Rehaily, Adnan J.; Siddiqui, Maqsood A.; Faisal, Mohammad; Ahmad, Javed; Alsaleh, Asma N.; Alatar, Abdulrahman A.; Al-Khedhairy, Abdulaziz A.
Graphical abstract: Highlights: First comparative anti-cancer study on persicogenin and homoeriodictyol. Flavanones induced apoptosis by novel p53 -dependent and p53 -independent mechanisms. Persicogenin and homoeriodictyol are active inducers of intracellular ROS. Flavanones selectively affect mitochondrial functionality (Δ Ψm ) of cancer cells. Both flavanones exhibit prospects of potential drugs for cancer treatment. Abstract: Herein we examined two flavanones (persicogenin and homoeriodictyol) isolated from Rhus retinorrhoea to elucidate the mechanism of their anticancer effects in MCF-7, HeLa, and HT-29 cells. Based on the [3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide)] (MTT) cytotoxicity data of persicogenin (500 μg/ml) caused a 58.1 % reduction in HT-29 survival while homoeriodictyol (500 μg/ml) caused a 51.9 %, 66.7 % and 76.2 % reductions in MCF-7, HeLa and HT-29 cell survival, respectively. The neutral red uptake (NRU) assay revealed 53.6 %, 53.9 %, 58.8 % and 83.0 %, 87.7 %, 66.7 % reductions in MCF-7, HeLa, and HT-29 cell survival following persicogenin and homoeriodictyol (500 μg/ml) treatment, respectively. Moreover, the intracellular reactive oxygen species (ROS) was significantly enhanced and dysfunction of mitochondrial membrane potential (Δ Ψm ) confirmed the mitochondrial injury in all cell types by the flavanones. MCF-7, HeLa, and HT-29 cells exposed to persicogenin and homoeriodictyol (500 μg/ml) had showed 42.5 %, 63.1 %, 62.3 % and 30.7 %, 30.2 %, 23.8 % cells in the sub G1 apoptotic phase. The persicogenin- and homoeriodictyol-treated cell lines had upregulated expressions of p53, caspase-3, caspase-9, bax, and superoxide dismutase 1 ( SOD1 ) genes. Such findings provide novel insight into the comparative anti-cancer efficacy of persicogenin and homoeriodictyol, signifying their promising clinical applications as cancer treatments and their application as bioactive therapeutic agents.